1998
DOI: 10.1128/iai.66.9.4411-4417.1998
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of a Pathogenicity Island in Uropathogenic Escherichia coli CFT073: Distribution of Homologous Sequences among Isolates from Patients with Pyelonephritis, Cystitis, and CatheterAssociated Bacteriuria and from Fecal Samples

Abstract: Urinary tract infection is the most frequently diagnosed kidney and urologic disease and Escherichia coli is by far the most common etiologic agent. Uropathogenic strains have been shown to contain blocks of DNA termed pathogenicity islands (PAIs) which contribute to their virulence. We have defined one of these regions of DNA within the chromosome of a highly virulentE. coli strain, CFT073, isolated from the blood and urine of a woman with acute pyelonephritis. The 57,988-bp stretch of DNA has characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…The malX gene, previously used as a marker for PAI‐I from strain CFT073 [2,12,25], was detected using PCR as previously described [2], but using a primer concentration of 0.6 μM. Carriage of the HPI was detected using a duplex PCR amplifying the genes fyuA and irp2 with previously published primer pairs [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The malX gene, previously used as a marker for PAI‐I from strain CFT073 [2,12,25], was detected using PCR as previously described [2], but using a primer concentration of 0.6 μM. Carriage of the HPI was detected using a duplex PCR amplifying the genes fyuA and irp2 with previously published primer pairs [26].…”
Section: Methodsmentioning
confidence: 99%
“…Such virulence genes are commonly located on particular regions of the bacterial chromosome called pathogenicity islands (PAIs) [11]. Two pathogenicity islands associated with E. coli strains of extra‐intestinal pathogenicity are PAI‐I, first identified in the uropathogenic E. coli strain CFT073, and the high‐pathogenicity island (HPI), thought to have spread from Yersinia [2,12]. The HPI is the most prevalent PAI among Enterobacteriaceae [13], and has been suggested to have been acquired early during evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using carboxylesterase B electrophoretic pattern (MLEE) indicated that they belong to the B2 group [17–21]. In this group, DNA fragments (named ‘pathogenicity‐associated islands’ or PAIs) have been recently identified, in or near [22] the tRNA genes, that encode P‐fimbria, 1‐fimbria, α ‐hemolysin, aerobactin and necrocytotoxic factor synthesis [23]. The presence of PAIs allows the bacteria to colonize squamous, transitional and renal tubular epithelia, avoid natural defense mechanisms, grow in adverse media, and provoke internalization by means of toxic actions on the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some PAIs are even strain specific. This could be demonstrated, for example, for PAI I 536 and PAI III 536 of the uropathogenic E. coli (UPEC) strain 536 and for PAI I CFT073 of the UPEC strain CFT073 (5, 6). Other PAIs are indicators for the more virulent strains of a certain pathogenic species such as the cag PAI of the most pathogenic Helicobacter pylori strains (7).…”
Section: Pais As Indicators For Virulent Bacterial Microorganismsmentioning
confidence: 94%